Gabinete de curiosidades: o paradoxo das maravilhas - Maria Lívia C. M. Ramos Gonçalves; Antonio Carlos Rodrigues de Amorim (Universidade Estadual Paulista Júlio de Mesquita Filho, 2012)
The Wunderkammern, cabinets of wonders or curiosities, are fairly cited as the origin of modern museums. The artist Walmor Correa made reference to these spaces in his installation entitled Memento mori, held in 2007 in Porto Alegre. We work with the images of this installation and references of Cultural Studies to consider the meanings of science, especially biology, put into circulation by this installation that evoke the cabinets. We walked between the powers that the wonders have to destabilizing the familiar hierarchies and the power that the well-known senses have to make the eccentricities (re)affirm the centrality,which they appear to be apart. Memento mori can multiply possibilities in the art-science between, questioning the centrality of normative rules, acting as political activity in the encounter art-science. And can also take a game which reforces classificatory systems, stereotype. And also suggest one more way, and another, e many others.